Article RETRACTED due to manipulation by the au ipThe effectiveness of effriction and frirage massage therapy in reducing pain in knee injuries: a comprehensive review of 1-month and 2-month injuries duration - Arif Setiawan; Andry Akhiruyanto; Sri Haryono; Zainul Aziz; Taufiq Hidayah; Rifqi; Iqbal Indra Awaludin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this study was to compare the effectiveness of effriction and frirage massage therapy methods in reducing pain in knee injuries. A total of 64 participants (Male, BMI = 21.48 kg/m2, Age ± SD = 24,07 ± 2.72), who were classified by 1-month and 2-month injury duration, underwent various therapy regimens with 10-minute and 15-minute treatment durations. The data collection instrument used the NPRS scale. The results of the analysis showed that the effriction intervention significantly reduced knee pain in injuries with a history of 1 month and 2 months, with a consistent reduction in pain at both 10 and 15 minute durations (p-value = 0.000). In contrast, frirage interventions also showed a reduction in pain, but their effectiveness varied; A significant reduction in pain was only observed at a 10-minute duration for a 1-month history injury (p-value = 0.041) and at a 15-minute duration for a 2-month history injury (p-value = 0.028). There was no significant reduction in pain in frirage with a duration of 10 minutes for 2 months of injury and a duration of 15 minutes for 1 month of injury. Overall, the effriction technique is more effective than frirage in reducing knee pain in traumatic injuries. These findings support the recommendation to use effriction as the primary method in knee pain therapy, while frirage may be considered for more specific contexts.